Synthesis of graphitic carbon from empty palm oil fruit bunches through single-step graphitization process using K2FeO4-KOH catalyst as lithium ion battery anode - Isnanda Nuriskasari; Anne Zulfia Syahrial; Tribidasari A. Ivandini; Afriyanti Sumboja; Bambang Priyono; Qingyu Yan; Fredina Destyorini; Slamet Priyono (Results in Engineering)
This research aims to optimize the graphitization process of carbon derived from Empty Palm Oil Fruit Bunches (EPOFB), a renewable biomass source, using a single-step K₂FeO₄-KOH impregnation-activation method. The results demonstrate that increasing the mass of K₂FeO₄, up to the optimal level, enhances the degree of graphitization, as confirmed by XRD and Raman spectroscopy. Optimal performance is observed with a catalyst mass of 0.11 g K₂FeO₄ in the C_ K₂FeO₄(0.11)KOH_800 sample, which exhibits a d002 spacing of 0.3356 nm, an IG/ID ratio of 2.42, a high surface area of 787.767 m²/g, and clearly defined graphitic layers in TEM images. Electrochemical testing of C_ K₂FeO₄(0.11)_KOH_800 reveals promising results, including the lowest charge transfer resistance (Rct) of 87.18 Ω, a significant area under the curve in cyclic voltammetry, a charging capacity of 330.3 mAh g⁻¹ at 0.1 C, with an excellent rate capability of 183 mAh g⁻¹ at 1 C after 100 cycles, maintaining a retention rate of 68.2 %. The single-step K₂FeO₄-KOH impregnation-activation method effectively enhances the graphitization of EPOFB-derived carbon, offering potential applications in high-performance lithium battery anodes.